Energy saving potential and energy audit of a faculty building at Marmara University in Turkiye - VARBAK NEŞE, SEÇİL; ÇALIŞ USLU, BANU; AKPOLAT, ALPER NABİ; DURSUN, ERKAN (My University, 2022)
According to the Council of Higher Education\"s records in 2022, one hundred thirty-one public universities operate in Turkiye. If the energy efficiency in faculty buildings is improved by 20%, 1.458 million U.S. dollars savings per year would be possible. This paper presents the energy profile and energy audit of the Faculty of Technology at Marmara University, in Istanbul Türkiye. The energy efficiency opportunities for faculty building are investigated depending on the energy audit results. The fact that the faculty building is uninsulated therefore this situation causes severe energy losses. The annual heating energy requirement of this university building, which has an average construction area of 15,000 m², is 297,728 kWh. Only an average of 56,987 kWh in fuel consumption and up to 20% energy savings can be achieved with thermal insulation. However, when the existing lighting fixtures are replaced with Light Emitting Diode (LED) fixtures, the annual savings amount is $6,198. The results of this study enable search of sustainable solutions for reducing energy consumption and improving energy audits for faculty buildings.
Keywords: Elektrik-Elektronik Mühendisliği; Enerji; Aydınlatma Teknolojisi; Güç Sistemlerinin Analizi; Mühendislik ve Teknoloji; Electrical and Electronics Engineering; Energy; Lighting Technology; Power System Analysis; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; Elektrik ve Elektronik Mühendisliği; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Enerji (çeşitli); Genel Enerji; Sinyal İşleme; Fizik Bilimleri; Electrical and Electronic Engineering; Renewable Energy, Sustainability and the Environment; Fuel Technology; Energy Engineering and Power Technology; Energy (miscellaneous); General Energy; Signal Processing; Physical Sciences